DAMPAK GAME ONLINE: STUDI FENOMENA PERILAKU TRASH-TALK PADA REMAJA - Nurul Warits Marinsa Putri; Hamiyati Hamiyati; Shinta Doriza (JURNAL PSIKOLOGI MALAHAYATI, 2020)
ABSTRACT: ONLINE GAME IMPACT: STUDY OF TRASH-TALK BEHAVIOR PHENOMENON IN  ADOLESCENTS Playing online games can trigger aggressive behavior. One of the phenomena of aggressive behavior among adolescents that occurs in Indonesia is trash-talk behavior. This research was conducted to find out the phenomenology of trash-talk behavior in adolescents and to understand the factors that cause trash-talk behavior. This research is a qualitative study using the Interpretative Phonomenological Analysis (IPA) method. The online game media chosen is the Bang Bang Legend Car Online Game (MLBB). The sample in this study were 3 people, where primary data were obtained from adolescents aged 14-15 years who were selected by purposive sampling. Data collection techniques were carried out through participatory observation, semistructured interviews, and documents. The results of this study indicate that there are 12 factors that cause teenagers to trash-talk behavior in the MLBB online game. By minimizing these twelve factors, it can prevent teenagers from the negative impact of trash-talk behavior and develop into a positive person. Keywords: Online Games Impact, Mobile Legends Bang Bang, Trash-Talk, Adolescent Behavior  Bermain game online dapat memicu perilaku agresif. Salah satu fenomena perilaku agresif pada remaja yang terjadi di Indonesia adalah perilaku trash-talk. Penelitian ini dilakukan untuk mencari tahu fenomenologi perilaku trash-talk pada remaja dan memahami faktor penyebab perilaku trash-talk. Penelitian ini adalah penelitian kualitatif dengan metode Interpretative Phonomenological Analysis (IPA). Media game online yang dipilih adalah Game Online Mobil Legend Bang Bang (MLBB). Sampel dalam penelitian ini sebanyak 3 orang, dimana data primer didapatkan dari remaja berusia 14-15 tahun yang dipilih secara purposive sampling. Teknik pengumpulan data dilakukan melalui observasi partisipasi, wawancara semiterstruktur, dan dokumen. Hasil penelitian ini menunjukkan terdapat 12 faktor penyebab remaja berperilaku trash-talk dalam game online MLBB. Dengan meminimalisir kedua belas faktor tersebut maka dapat menghindari remaja dari dampak negative perilaku trash-talk dan berkembang menjadi pribadi yang positif. Kata kunci : Dampak game online, Mobile Legends Bang Bang, Trash-Talk, Perilaku Remaja